Transient Pancytopenia Subsequently Diagnosed With Acute Leukemia: A Report of 4 Cases of Acute Lymphoblastic Leukemia and Acute Myeloid Leukemia. Issue 5 (26th July 2021) - Kirk, Susan E.; Young, Elizabeth; Ray, Anish; Dzurik, Yvette; Elghetany, Tarek; Sasa, Ghadir
Abstract : A transient pancytopenic phase has been described in pediatric leukemia. The characteristic complete recovery of peripheral counts can obscure a clinician's suspicion for malignancy and may impact subsequent follow-up care. The authors describe 4 pediatric patients that had transient pancytopenia with an initial abnormal marrow finding. These patients were subsequently diagnosed with acute leukemia within 5 months of presentation. Awareness of this phenomenon by the provider and education of families may help with the appropriate and timely diagnosis of subsequent leukemia.